The Impact of Investment Climate on Industrial growth in the Central African sub-region (CEMAC) - Peter Angyie, Dr. Etoh-Anzah; Martial Annicet, Mr. Badjo Ngongue (International Journal of Scientific Research and Management (IJSRM), 2020)
The study on the Impact of Investment Climate on Industrial growth in the Central African sub-region (CEMAC) is centered on investigating into how macroeconomic stability, rule of law, political stability, legal and tax framework, infrastructure, and access to financial services will impact on industrial growth in the CEMAC region. It used data from World Development Indicators and World Governance Indicators database of the World Bank for 2002 to 2017 for all 6 countries of the sub region. Using the system-generalized method of moments (System-GMM) model and the fixed effects generalized least squares estimation techniques, our results on the average revealed that investment climate positively though not significantly, impact on the industrial growth in the sub region during the study period. However, up to about 45.5 per cent of the variables used for investment climate showed a negative impact on the industrial growth of the sub region. We therefore recommend that bureaucracy, government effectiveness, the type of government expenditure under taken, trade openness and value accountability be revisited and appropriate measures taken to permit for important improvements in industrial growth in the sub region.